2010
DOI: 10.1016/j.bpj.2010.02.030
|View full text |Cite|
|
Sign up to set email alerts
|

Kinetics of Regulated Actin Transitions Measured by Probes on Tropomyosin

Abstract: Changes in the muscle regulatory protein complex, troponin, are important for modulation of activity and may occur as a result of disease-causing mutations. Both increases and decreases in the rate of ATP hydrolysis by myosin may occur as dictated by changes in the distribution of actin-tropomyosin-troponin among its different states. It is important to measure the rates of transition among these states to study physiological adaptation and disease processes. We show here that acrylodan or pyrene probes on tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
56
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(65 citation statements)
references
References 45 publications
6
56
3
Order By: Relevance
“…This may suggest that crossbridge detachment observed by TnC IANBD T53C is sensed and limited by movement of another myofilament protein (tropomyosin (Tm), TnI, or TnT) or that the rate of cross-bridge detachment from the nucleotide free myofibrils is slower than that measured from reconstituted actomyosin. The idea that Tm movement may limit the observed rate of cross-bridge detachment is consistent with skeletal thin filament studies where myosin detachment was Ͼ500/s as measured by light scatter but sensed at ϳ200/s by a fluorescent Tm (47). However, by following a change in Trp fluorescence, ATP also hyperbolically accelerated the rate of cross-bridge detachment in skeletal myofibrils (in the absence of ADP) (36).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This may suggest that crossbridge detachment observed by TnC IANBD T53C is sensed and limited by movement of another myofilament protein (tropomyosin (Tm), TnI, or TnT) or that the rate of cross-bridge detachment from the nucleotide free myofibrils is slower than that measured from reconstituted actomyosin. The idea that Tm movement may limit the observed rate of cross-bridge detachment is consistent with skeletal thin filament studies where myosin detachment was Ͼ500/s as measured by light scatter but sensed at ϳ200/s by a fluorescent Tm (47). However, by following a change in Trp fluorescence, ATP also hyperbolically accelerated the rate of cross-bridge detachment in skeletal myofibrils (in the absence of ADP) (36).…”
Section: Discussionsupporting
confidence: 79%
“…In the absence of ADP, ATP-induced detachment of myosin from reconstituted skeletal and cardiac actomyosin is extremely fast (Ͼ500/s) (15,47). This may suggest that crossbridge detachment observed by TnC IANBD T53C is sensed and limited by movement of another myofilament protein (tropomyosin (Tm), TnI, or TnT) or that the rate of cross-bridge detachment from the nucleotide free myofibrils is slower than that measured from reconstituted actomyosin.…”
Section: Discussionmentioning
confidence: 99%
“…Acrylodan-labeled and pyrene-labeled smooth muscle tropomyosin were prepared as described for skeletal muscle tropomyosin (24) using a 10:1 molar ratio of acrylodan or N-(1-pyrene)iodoacetamide to tropomyosin. These conditions gave >70% labeling using extinction coefficients of 22,000 M −1 cm −1 at 344 nm for pyrene and 14,400 M −1 cm −1 at 372 nm for acrylodan (33).…”
Section: Methodsmentioning
confidence: 99%
“…The differential equations used to simulate the ATP dissociation studies (Model A) were shown earlier (24). S1-ATP detachment was simulated by examining the change of ATP-M-A with time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation